PENGEMBANGAN PURWARUPA ROBOT PEMADAM API DENGAN KENDALI BERBASIS MIKROKONTROLER - Mochammad Safarudin; Abdul Patah (Sekolah Tinggi Teknologi Mandala Bandung, 2020)
Since the last few decades, the role of robots in industry and daily life is increasing, fire fighting robots are autonomous ground vehicles that are widely designed for research, industry and robot competition, as the name suggests the task of this robot is to detect the presence of flames in a room and then extinguish them, The process of finding fire points using flame sensors, servo motors are used as wheel drive motors and fan modules as fire extinguishers. Microcontrolles used are microcontrolle atmega32 board arduino Uno R3 as robot control and arduino nano as location detection program, GPS module as location detector, ultrasonic sensor as obstruction detector and sim module 800 l as sending media location coordinate point. The research method used is Research and Development which is often interpreted as a process or steps to develop a new product or improve an existing product. Software used for robot programming using arduino IDE 1.8 application. The robot is designed to have three wheels, two rear wheels and one wheel in the front center, for the frame material uses solid acrylic black color with a thickness of 3 mm, the main frame length is 18 cm and width of 4 cm, the size of the wheel diameter and tire is 8 cm, the height of the sensor buffer is 7 cm and the width is 2 cm, for the track size has a width of 25 cm and a wall height of 15 cm , the height of the candle is 10 cm and the distance between the candle and the wall is 4 cm. The approach used is quantitative with experimental research methods. at the experimental stage of the control variables (inputs) to analyze the resulting output. In this Final Task, percompponent testing is performed to ensure the components run according to their functionality and overall testing. The result of this study is a fire extinguishing robot that can move automatically avoiding obstacles and equipped with gps systems.